Cloning of eukaryotic expression cassette into pMG36e Lactococcal vector - Lim, Yi Yi (2015)
Lactococcuslactis(L. lactis) is a Gram-positive bacteria traditionally used in food industry for flavouring and fermenting processes. In recent years, L. lactis was found to be able to deliver plasmid DNA into eukaryotic cells and express heterologous protein, which makes it being developed as safer alternative for vaccination. The increasing demand of L. lactisbeyond application in food industry raises the need to develop lactococcal bicistronic vector with target gene expression in the eukaryotic system. The objective of this study is to construct a lactococcal vector containing modified eukaryotic expression cassette, with internal ribosome entry site (IRES) inserted between CMV promoter and Poly A signal to allow transcription and translation of two proteins in a single cassette. IRES sequence was PCR-amplified from pRetroX-IRES-ZsGreen1 vector, digested with EcoRV and XhoI, and ligated into eukaryotic expression cassette from pcDNA 3.1 HisA. Constructed vector was transformed into E. coli TOP 10 and the orientation of IRES fragment in the modified eukaryotic expression cassette was confirmed by DNA sequencing. The modified eukaryotic expression cassette was PCR-amplified from pcDNA3.1HisA/IRES before sub-cloning into lactococcal vector pMG36e.pMG36eharbouringmodified eukaryotic expression cassette was successfully transformed into E. coli TOP 10 but not L. lactis NZ9000. Optimization of transformation protocol for L. lactis NZ9000 using electroporation is needed to enhance transformation efficiency. Segragational instability of constructed vector in E. coli host was detected, which may have been caused by production of single-stranded intermediates and high-molecular weight DNA due to rolling-cycle replication of the pMG36e vector.